Do financial incentives alter physician prescription behavior? Evidence from random patient-GP allocations - Alexander Ahammer; Ivan Zilic (Johannes Kepler University of Linz, Department of Economics, 2017)
Do physicians respond to financial incentives? We address this question by analyzing the prescription behavior of physicians who are allowed to dispense drugs themselves through onsite pharmacies. Using administrative data comprising over 16 million drug prescriptions between 2008 and 2012 in Upper Austria, a näive comparison of raw figures reveals that self-dispensing GPs induce 33.2% higher drug expenses than others. Our identification strategy rests on multiple pillars: First, we use an extensive array of covariates along with multi-dimensional fixed effects which account for patient and GP-level heterogeneity as well as sorting of GPs into onsite pharmacies. Second, we use a novel approach that allows us to restrict our sample to randomly allocated patient-GP matches which rules out endogenous sorting as well as principal-agent bargaining over prescriptions between patients and GPs. Contrary to our descriptive analysis, we find evidence that onsite pharmacies have a small negative effect on prescriptions. Although self-dispensing GPs seem to prescribe sligthly more expensive medication, this effect is absorbed by a much smaller likelihood to prescribe something in the first place, causing the overall effect to be negative.
Keywords: I11; I12; 330; physician dispensing; drug expenses; physician agency; moral hazard